Behavior-specific praise: empowering teachers and families to support students in varied learning contexts. Issue 2 (3rd April 2023) - Pérez, Paloma; Gil, Haley; Artola, Arabiye; Royer, David James; Lane, Kathleen Lynne
Abstract: In this article, we introduce behavior-specific praise as a portable, feasible strategy for teachers and families to increase student engagement as well as to decrease off-task and disruptive behaviors in a variety of environments. We provide step-by-step guidance to illustrate how behavior-specific praise can be used by teachers during in-person and remote learning environments and how families can incorporate behavior-specific praise into daily routines at home.